A study on the standard procedure and employee satisfaction towards the level of effectiveness in conducting performance appraisal based on employees perception at school of medical sciences, Universiti Sains Malaysia (USM) / Hashimah Wardah Baruddin - Baruddin, Hashimah Wardah (Faculty of Business and Management, 2018)
Performance appraisal is one of the methods to measure the employee performance. The objective of this research is to study the perception of employee towards the level effectiveness of conducting performance appraisal at School of Medical Sciences~ USM. Performance appraisal always facing pitfalls because of employee not satisfied with the performance appraisal at their organization. For some employee, performance appraisal as dishonest appraisal and lead them dissatisfied. In this study, the most factor that affect the level effectiveness of performance appraisal is the standard procedure that apply at School of Medical Sciences~ USM. This study was using correlation research method. The simple size was using Sekaran (2003) and simple random sampling has been selected for this study. The finding shown that~ standard procedure has moderate relationship with the level of effectiveness performance appraisal. Meanwhile employee satisfaction have weak relationship with the level of effectiveness performance.